Short-term borrowing for long-term projects: Are family businesses more susceptible to 'irrational' financing choices? - Bettina Peters; Peter Westerheide (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
There are noticeable differences between the roles that various forms of credit financing play in family businesses and in other businesses. Family businesses take out more often bank loans specifically to finance investments and innovations, and they particularly often resort to the short-term and relatively expensive option of an overdraft. How can we explain these differences in financing choices? Do family businesses tend to use shorter-term, more expensive sources of financing because they face more restrictions than other or are there other motives such as financial independence at play? Our econometric approach to these issues is to study the financing behaviour and creditworthiness. For both of these aspects, we compare family businesses with non-family-run businesses that otherwise have the same characteristics. Our results do not confirm that family businesses are faced by stronger financial constraints but they indicate that family firms are prepared to accept higher financing costs in order to preserve their financial independence.
Keywords: G32; G31; M14; 330; Corporate financing; innovation; family businesses; financing restrictions